ASUPAN ZAT BESI (Fe) DAN BERAT BADAN LAHIR TERHADAP PERKEMBANGAN MOTORIK ANAK USIA 3-5 TAHUN - Damayanti, Ariani (Indonesian Journal of Nutrition Science and Food; Vol 1 No 2 (2022): Januari 2022, 2022)
Motor development is one aspect that needs to be considered in the growth and development of toddlers. Several factors that can affect child's motor development include iron intake and birth weight. This study aims to determine relationship between iron intake, birth weight and motor development of children aged 3-5 years. The subjects of this study were 97 preschool children aged 3-5 years in Gayamsari District. This study used a cross sectional method with a stratified random sampling technique. Iron intake data was obtained from a 3 x 24 hours recall, then processed by nutrisurvey. Motor development data was measured using Denver Development test II. Data were analyzed by descriptive test, Chi Square and Fisher Exact. There were 52 children (53,6%) with low iron adequacy level and 10 children (10,3%) with low birth weight. Statistical tests showed that there was a relationship between iron intake and fine motor development (p = 0,01), no relationship with gross motor development (p = 0,41) and no relationship between birth weight and fine and gross motor development (p = 0,71 and p = 1). The conclusion of the study is that iron intake has an important role in child development, especially fine motor development.